Divalent cation regulation of the surface orientation of platelet membrane glycoprotein IIb. Correlation with fibrinogen binding function and definition of a novel variant of Glanzmann's thrombasthenia. - Ginsberg, M H (1986)
An antiplatelet monoclonal antibody, PMI-1, reacts with glycoproteins (GP) GPIIb, free GPIIb, and the GPIIb-IIIa complex. This antibody binds to 40,900 sites per platelet, with a Kd = 0.95 microM, and its binding is inhibited by the presence of magnesium or calcium in the suspending medium (50% suppression at approximately 0.5 mM divalent cation). Regulation of the PMI-1 epitope is independent of disassembly of the GPIIb-IIIa heterodimer, because it occurred at 22 degrees C and in response to mM magnesium as well as calcium. PMI-1 binding inversely correlated with fibrinogen binding. In addition, we identified a variant of Glanzmann's thrombasthenia with near-normal platelet content of the GPIIb-IIIa heterodimer as judged by crossed immunoelectrophoresis and surface labeling. Binding of PMI-1 to these patients' platelets was not dependent on reduction of the divalent cation concentration. These data suggest that the surface orientation of GPIIb is important in the capacity of platelets to bind fibrinogen.